An OVERVIEW OF ANTIHYPERTENSION MEDICATION USE IN HYPERTENSION PATIENTS IN THE OUTPATIENT UNIT BALADHKA HUSADA HOSPITAL - Shyntia Aurelia Fajratul Hikmah; Iski Weni Pebriarti; Jamhariyah (LPPM Universitas dr. Soebandi, 2025)
ABSTRACT Background: Hypertension is one of the cardiovascular diseases characterized by systolic blood pressure >140 mmHg and diastolic blood pressure >90 mmHg. This condition poses the highest risk as the leading cause of death due to cardiovascular diseases in Indonesia. According to Riskesdas data in 2018, the prevalence of hypertension in Indonesia reached 34.1%, an increase compared to Riskesdas 2013 at 25.8%. The management of hypertension can be conducted through pharmacological and non-pharmacological therapies. Pharmacological therapy involves the use of various classes of antihypertensive drugs tailored to each patient's clinical condition. Objective: This study aims to analyze the use of antihypertensive drugs based on the type of therapy, drug class, drug name, and the doses prescribed to hypertension patients in the outpatient unit of Baladhika Husada Hospital. Method: The samples for this study were collected using a simple random sampling technique. Results: The study conducted at Baladhika Husada Hospital in Jember during the period from September to November 2023, involving a total of 77 patient samples, showed that the most commonly used therapy was a combination of three drugs, found in 53 prescriptions (68.83%). The most commonly used drugs belonged to the beta-blocker class, specifically bisoprolol at a dose of 2.5 mg. Conclusion:The most dominant therapy for hypertension involves the combination of three drugs. The most frequently prescribed drug class is beta-blockers, with bisoprolol at a dose of 2.5 mg being the most widely used drug. Keywords: antihypertensive; hospital; hypertension; outpatient